Hubungan Antara Status Gizi Dengan Kejadian Anemia Pada Remaja Putri - Miptakul Janah; Surati Ningsih-Politeknik Kesehatan Bhakti Mulia (Indonesian Journal on Medical Science, 2021)
Abstract: A girl had a higher risk to get anemia because they consumed food that have a lower iron, usually girl wanted to look slim so that they limited to eaten food and girl had menstruation every month. If the habit of their eaten wrong will give rise to a problem like have a skinny body and indication of anemia. This research had a goal for find out the relation between nutritional status with indication of anemia on the girl. This research uses observational analityc methods with have approach on cross sectional of the seventy nine respondents. The process of taking the respondents was held by purposive sampling methods and data collection that use a scale, microtoise and digital hemometer. Research results of seventy nine respondents showed that most of them had an abnormal nutritional status which is they had a skin body 31(39,2%) and fat 11(14,0%). And almost half of all respondents got a indication of anemia. Data analysis results with chi square test (xÂ²) showed that there was a relation between nutritional status with indication of anemia with p value= 0,000 (<0,05), r hitung(34,700) > r tabel(5,991). Girl who had a skin body tend havean indication of anemia and girl who had a normal nutritional status and who had a fat body tend haven't an indication of anemia.Keywords : nutritional status, anemia, adolescent girlsÂ Abstrak : Remaja putri mempunyai resiko lebih tinggi mengalami anemia karena mereka mengkonsumsi makanan yang zat besinya sedikit, serta remaja putri mengalami menstruasi setiap bulan. Jika kebiasaan makannya sering keliru akan menimbulkan masalah yaitu status gizi yang kurus dan mengalami anemia. Penelitian ini bertujuan untuk mengetahui hubungan antara status gizi dengan kejadian anemia pada remaja putri ]. Penelitian ini menggunakan metode observasional analitik dengan pendekatan cross sectional terhadap 79 responden. Pengambilan responden dilakukan dengan metode purposive sampling dan pengumpulan data menggunakan timbangan, microtoise dan hemometer digital. Hasil penelitian dari 79 responden menunjukkan sebagian besar memiliki status gizi abnormal yaitu kurus 31(39,2%) dan gemuk 11(14,0%). Dan hampir setengah dari jumlah responden mengalami anemia (43,0%). Hasil analisa data dengan uji chi square ( 2)menunjukkan ada hubungan antara status gizi dengan kejadian anemia dengan pvalue = 0,000 (<0,05), rhitung (34,700) > rtabel (5,991). Remaja putri yang mempunyai status gizi kurus cenderung mengalami anemia dan remaja putri dengan status gizi normal dan gemuk cenderung tidak mengalami anemia.Kata kunci : status gizi, anemia, remaja putri